2017
DOI: 10.1111/apt.14285
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the association between hepatitis E seroprevalence and haemodialysis

Abstract: Hepatitis E virus infection is more prevalent in patients on haemodialysis compared with non-haemodialysis control groups. Further studies are needed to determine risk factors of acquisition, impact on health, and risk for chronic HEV especially among those patients going to receive organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
(97 reference statements)
1
20
0
Order By: Relevance
“…The reported prevalence of anti‐HEV IgG ranges from 6% to 16% among renal transplant recipients in developed countries . Rates of HEV seroprevalence in patients on maintenance dialysis are higher than in healthy controls, probably because of administration of blood products . Based on HEV‐RNA detection, the incidence of HEV infection varies from 0.9% to 3.5% in solid organ transplant (SOT) recipients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of anti‐HEV IgG ranges from 6% to 16% among renal transplant recipients in developed countries . Rates of HEV seroprevalence in patients on maintenance dialysis are higher than in healthy controls, probably because of administration of blood products . Based on HEV‐RNA detection, the incidence of HEV infection varies from 0.9% to 3.5% in solid organ transplant (SOT) recipients .…”
Section: Introductionmentioning
confidence: 99%
“…maintenance dialysis are higher than in healthy controls, probably because of administration of blood products. 22 Based on HEV-RNA detection, the incidence of HEV infection varies from 0.9% to 3.5% in solid organ transplant (SOT) recipients. 23 It has been reported that 60% of SOT recipients with viremic HEV infection progress to chronic infection defined as persistence of HEV-RNA for more than 6 months.…”
mentioning
confidence: 99%
“…A human vaccine has already been approved in China in December 2011, and it is believed that a swine vaccine is feasible . Other described risk factors include infected water, shellfish, blood transfusions and haemodialysis …”
Section: Discussionmentioning
confidence: 99%
“…60 Other described risk factors include infected water, shellfish, blood transfusions and haemodialysis. 62,63 HEV-RNA testing is the gold standard for diagnosis of ongoing infection. The virus is detectable in the blood and stool just before the onset of hepatitis symptoms of acute hepatitis, and disappears from the blood within 3 weeks, while persisting in the stool for 2 more weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[48] According to the Department for Environment, Food and Rural Affairs, evidence indicated the increase in hepatitis E in the U.K. was due to food-borne zoonoses, citing a study that found in the U.K. that 10% of pork [39] Hepatitis E infection appeared to be more common in people on hemodialysis, although the specific risk factors for transmission are not clear. [49] Animal reservoir…”
Section: Infection In Pregnancymentioning
confidence: 99%